ANALYSIS OF STORE ATMOSPHERE, REFERENCE GROUP, AND LIFESTYLE ON CONSUMER PURCHASING DECISIONS STARBUCKS COFFEE IN BANDAR LAMPUNG - Auliyanti, Riska (Jurnal Kompetitif Bisnis, 2021)
Abstract This study aims to determine the effect of store atmosphere, reference group, and lifestyle on consumer purchasing decisions of Starbucks Coffee in Bandar Lampung. This research uses a quantitative approach with a purposive sampling technique. The sample consisted of 100 respondents of Starbucks Coffee customers in Bandar Lampung who had been to Starbucks Coffee and had a Starbucks member card. Data obtained from a questionnaire using a Likert scale. The data analysis in this study used descriptive data analysis and multiple linear regression analysis. The results of this study showed that the store atmosphere, reference group, and lifestyle partially and simultaneously have a positive and significant effect on purchasing decisions. The highest factor influencing purchasing decisions is the store atmosphere. Starbucks is expected to improve aspects that support the store atmosphere, maintain quality products and do not damage the environment, and continue to promote Starbucks products as eco-friendly products in accordance with the principle of Starbucks Coffee. Keyword: Store Atmosphere, References Group, Lifestyle and Purchasing Decisions